2015
DOI: 10.1186/s13054-014-0721-8
|View full text |Cite|
|
Sign up to set email alerts
|

Diminished adrenal sensitivity to endogenous and exogenous adrenocorticotropic hormone in critical illness: a prospective cohort study

Abstract: IntroductionAdrenal dysfunction may represent critical illness-related corticosteroid insufficiency (CIRCI), as evidenced by a diminished cortisol response to exogenous adrenocorticotropic hormone (ACTH), but this concept and its clinical significance remain highly controversial. We studied the adrenal response to exogenous ACTH as a function of the endogenous cortisol-to-ACTH ratio, a measure of adrenal sensitivity, and of clinical variables, during critical illness and recovery from the acute phase.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(200 citation statements)
references
References 32 publications
6
191
3
Order By: Relevance
“…The lower the cost of an intervention compared to the alternative and other costs related to the decision-i.e., fewer resources consumed-the more likely a strong recommendation prospective cohort studies in adults with or without sepsis [11] and in patients with multiple trauma [12] found that patients with CIRCI, i.e., total cortisol levels <10 µg/ dl or delta cortisol <9 µg/dl, had poorer outcomes than patients without CIRCI. Likewise, a large multicenter prospective cohort study found that critically ill children with a delta cortisol <9 µg/dl after the low-dose ACTH stimulation test required higher-dose and prolonged treatment with catecholamines, a higher amount of fluid, and had a higher mortality rate [13].…”
Section: Rationalementioning
confidence: 99%
“…The lower the cost of an intervention compared to the alternative and other costs related to the decision-i.e., fewer resources consumed-the more likely a strong recommendation prospective cohort studies in adults with or without sepsis [11] and in patients with multiple trauma [12] found that patients with CIRCI, i.e., total cortisol levels <10 µg/ dl or delta cortisol <9 µg/dl, had poorer outcomes than patients without CIRCI. Likewise, a large multicenter prospective cohort study found that critically ill children with a delta cortisol <9 µg/dl after the low-dose ACTH stimulation test required higher-dose and prolonged treatment with catecholamines, a higher amount of fluid, and had a higher mortality rate [13].…”
Section: Rationalementioning
confidence: 99%
“…In a prospective trial, Ricci et al randomized infants with congenital heart disease to receive either furosemide or ethacrynic acid following elective cardiac surgery. They found that ethacrynic acid was slightly more effective at augmenting urine output without any significant differences in post-operative serum creatinine or incidence of AKI (based on pRIFLE) (31). In a study of 30 pediatric patients with congestive heart failure already receiving inotropic and diuretic therapy, administration of synthetic B-type natriuretic peptide resulted in improved diuresis without significant increase in S Cr (32).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently recommendations in the Surviving Sepsis Guidelines emphasize the importance of lactate clearance during the resuscitation of septic patients [18]. Associations between depressed SE parameters and lactate in this study may lend insights on the mechanical contribution of cardiac dysfunction to hyperlactatemia in the context of the current literature [34, 35, 42]. Therefore further investigation into the utility of SE as a noninvasive assessment tool for cardiac function in children with sepsis is potentially useful.…”
Section: Discussionmentioning
confidence: 84%